A three-dimensional visualization of the full-field surgical region based on thin-slice MRI: A helpful approach for simultaneously guiding tumor resection and perforator flap elevation - Cui, Lei; Jiang, Wei Q.; Zhang, De K.; Wang, Gao F.; Han, Yu D.; Pu, Wen W.; Shao, Yan; Guo, Lin L.; Tao, Ran; Han, Yan (Frontiers in Surgery, 2022)
Background The goal of the current study was to explore the application of preoperative three-dimensional reconstruction (3DR) based on thin-slice magnetic resonance imaging (MRI) in the simultaneous guidance of en bloc tumor resection and adjacent perforator flap elevation. Methods The prospective cohort included 35 patients diagnosed with either soft tissue sarcoma or squamous cell skin cancer between 2019 and 2021. The preoperative 3DR based on thin-slice MRI illustrated the spatial anatomical relationship among the tumor, underlying muscle, adjacent perforator vessels, and bone around the surgical region. The accuracy of preoperative imaging data was verified by intraoperative vessel dissection and postoperative pathological measurements. Results Tumor size from 3DR data showed relatively high concordance rates with pathological measurements within the 95% limits of agreement. An average of three perforators (range: 1–7) with a mean diameter of 0.32 cm (range: 0.18–0.74 cm) from the 3DR were present in our study. The average distance between tumor boundary and perforator piercing sites on the 3DR was 2.2 cm (range: 1.2–7.7 cm). The average length of artery perforator coursing along the subcutaneous tissue was 5.8 cm (range: 3.3–25.1 cm). The mean flap harvest time was 55 mins (range: 36–97 min). The average flap size was 92.2 cm2 (range: 32–126 cm2). One perforator flap occurred distal partial necrosis. Conclusion A thorough understanding of anatomical structures in the surgical region according to full-field 3DR based on thin-slice MRI can improve the performance of radical resection of the tumor and adjacent perforator flap transfer, especially for junior surgeons with a poor experience.